Preparation process of graphite negative electrode material for unmanned aerial vehicle battery
Patent Information
- Application Number
- CN202611440327.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]为了改善无人机电池用石墨负极材料的倍率性能、循环寿命差的问题,本申请提供了一种无人机电池用石墨负极材料的制备工艺
1、本申请三级粒度级配,高压实密度,提升单体电芯能量密度,延长无人机续航,硝酸、高锰酸钾氧化,边缘活化,锂离子传导更快,满足无人机大电流放电、瞬时功率输出。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the technical field of lithium-ion batteries, and in particular to a preparation process of a graphite anode material for drone batteries. Background Technology
[0002] Lithium-ion batteries are widely used in portable electronic devices, transportation power, energy storage systems, and special and emerging applications due to their advantages such as high operating voltage, high energy density, long cycle life, low self-discharge, and no memory effect. Electric drones place comprehensive requirements on power lithium batteries, including high energy density, instantaneous high-rate discharge, long cycle life, and high safety and stability.
[0003] Natural flake graphite is currently the main active material for lithium-ion battery anodes due to its low cost, stable lithium intercalation / deintercalation platform, and good cycle stability. However, conventional unmodified natural graphite still has significant drawbacks. The graphite crystals are anisotropic, and lithium ions can only be intercalated from the edge sites of the flakes. The lithium ion diffusion rate is limited, resulting in insufficient high-rate discharge kinetics and making it difficult to match the instantaneous high-power output requirements of drones.
[0004] To overcome the performance bottleneck of graphite anodes, surface coating modification is a common technique. By coating the graphite surface with a layer of amorphous carbon, surface defects are modified, specific surface area is reduced, and side reactions are decreased, thereby improving initial efficiency and cycle stability. However, the theoretical capacity and true density of amorphous carbon are lower than those of graphite. An excessively thick coating layer will reduce the specific capacity by increasing the lithium-ion diffusion distance, and an excessively thick coating layer will hinder lithium-ion diffusion, resulting in poor performance during high-current charge and discharge.
[0005] Therefore, developing a preparation process for graphite anode materials for drone batteries that combines high real density, high rate discharge capability, high energy density, and excellent cycle stability has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] To improve the poor rate performance and cycle life of graphite anode materials used in drone batteries, this application provides a preparation process for graphite anode materials used in drone batteries.
[0007] This application provides a preparation process for graphite anode material for drone batteries, employing the following technical solution: A process for preparing a graphite anode material for drone batteries includes the following steps: oxidizing graphite with nitric acid and potassium permanganate, wherein the graphite particle size includes: 18-22 wt% particles with a particle size of 8-12 μm, 28-32 wt% particles with a particle size of 20-25 μm, and 48-52 wt% particles with a particle size of 15-18 μm.
[0008] By adopting the above technical solution, 8-12μm particles account for 18-22 wt%, fine particles that fill gaps, increase compaction density, and shorten the lithium-ion diffusion path; 15-18μm particles account for 48-52 wt%, the main aggregate and primary conductive framework, increasing density; and 20-25μm particles account for 28-32 wt%, large particles that reduce specific surface area, decrease electrolyte side reactions, and provide more lithium storage space. The particle size distribution exhibits a gradient, meeting the high compaction density, moderate specific surface area, fast-charging performance, and long cycle life requirements of drone power batteries. The three-stage gradation achieves tight particle packing, improving electrode compaction without significantly increasing specific surface area and reducing the risk of battery gas expansion.
[0009] Under acidic conditions, potassium permanganate generates highly oxidizing MnO4⁻, introducing oxygen-containing functional groups such as carboxyl and hydroxyl groups into the graphite surface. These groups significantly improve the dispersibility of graphite in aqueous or polar solvents, laying a good chemical bond foundation for subsequent operations. Potassium permanganate lightly etches the graphite edges, opening a small number of interlayer channels, shortening the lithium-ion diffusion path, and improving fast-charging capability. Nitric acid provides an acidic environment, enhancing the oxidation activity of potassium permanganate, while also dissolving trace metal impurities such as iron and nickel from the graphite, reducing battery self-discharge. Nitric acid molecules embed into the graphite interlayer, forming graphite interlayer compounds, physically widening the interlayer spacing, reserving wider channels for subsequent rapid lithium-ion insertion and extraction, and improving the high-rate discharge performance of drone batteries.
[0010] This application features a three-stage particle size distribution and high-density lithium-ion exchange, which improves the energy density of individual battery cells and extends the drone's endurance. Oxidation with nitric acid and potassium permanganate activates the edges, resulting in faster lithium-ion conduction and meeting the requirements for high-current discharge and instantaneous power output of drones.
[0011] Preferably, the graphite is subjected to oxidation treatment as follows: natural flake graphite is added to concentrated nitric acid, stirred in an ice-water bath, potassium permanganate is slowly added, stirring is continued, the temperature is lowered to room temperature, dilute hydrochloric acid is added to the precipitate, the mixture is stirred thoroughly, centrifuged, washed with deionized water, dried, and calcined to obtain activated graphite.
[0012] By employing the above technical solutions, the system temperature is controlled within an ice-water bath, thereby controlling the reaction rate and preventing excessively vigorous reactions. In strong oxidation reactions, low temperatures effectively prevent graphite from being over-oxidized or even burned, making the oxidation reaction more gentle and controllable. Low temperatures also inhibit the deep penetration of potassium permanganate into the graphite layers, preventing significant expansion of interlayer spacing and protecting the main crystal structure of graphite. Introducing oxygen-containing functional groups such as carboxyl and hydroxyl groups onto the particle surface improves electrolyte wettability, reduces interfacial impedance, and adapts to the high-rate instantaneous discharge requirements of drones.
[0013] Dilute hydrochloric acid reacts with manganese dioxide to convert insoluble manganese dioxide into soluble manganese ion salts, dissolving and washing away manganese impurities adsorbed on the graphite surface; manganese residues can cause metal deposition at the negative electrode of lithium batteries, resulting in lithium plating, self-discharge, and short circuits, seriously threatening the safety of drone batteries; calcination shortens the lithium ion diffusion path, significantly improving high-rate discharge performance and adapting to the high-power output of drones during takeoff.
[0014] Preferably, the ratio of natural flake graphite, potassium permanganate, and concentrated nitric acid is 1g:0.1-0.2g:10-11mL.
[0015] By adopting the above technical solution, the main framework for lithium ion insertion and extraction in natural flake graphite is achieved. Potassium permanganate attacks the graphite layer with strong oxidizing properties, introducing oxygen-containing functional groups on its surface and edges, weakening the van der Waals forces between graphite layers, and slightly etching to open edge channels, shortening the lithium ion diffusion path, improving high-rate discharge performance, and adapting to the instantaneous high-power output of drones during takeoff.
[0016] Concentrated nitric acid-assisted oxidation of graphite with potassium permanganate allows its molecules or ions produced by decomposition to insert into the interlayer spaces of the oxidized graphite, thus increasing the interlayer spacing. This increased interlayer spacing provides a smoother pathway for lithium ions, which is beneficial for improving the battery's rate performance (fast charging capability). Intercalation also enhances the material's reversible capacity and cycle stability.
[0017] Preferably, sulfuric acid can also be added for oxidation treatment. The specific operation steps are as follows: In an ice-water bath, concentrated nitric acid and concentrated sulfuric acid are slowly mixed and stirred evenly. Natural flake graphite is added and stirred in an ice-water bath. Potassium permanganate is then added and stirred. Deionized water and hydrogen peroxide are added in an ice-water bath until the solution turns bright yellow or light green and no bubbles are produced. After centrifugation, the supernatant is discarded. Dilute hydrochloric acid is added to the precipitate, and the mixture is thoroughly stirred and washed. The precipitate is then dried and calcined to obtain activated graphite.
[0018] By employing the above technical solution, concentrated sulfuric acid and concentrated nitric acid are mixed to form more reactive species such as nitro cations, which can oxidize graphite more efficiently and introduce more functional groups. In the strongly acidic environment of sulfuric acid, potassium permanganate can be further activated to react and generate manganese heptaoxide, which has extremely strong oxidizing properties. This in-situ generated highly reactive species can oxidize graphite more deeply and uniformly.
[0019] The synergistic intercalation of sulfuric acid and nitric acid molecules can more effectively widen the interlayer spacing of graphite, creating space for subsequent reactions and lithium-ion transport. Sulfuric acid can form more stable sulfuric acid-graphite interlayer compounds. Mixed acid impregnation of graphite is more thorough, improving the uniformity of modification between particles, slightly increasing the interlayer spacing at the edges, making the initial lithium intercalation channels more unobstructed, deepening the activation depth at the graphite edges, reducing lithium-ion diffusion resistance, and improving high-rate discharge performance, making it suitable for the high-power output during drone takeoff.
[0020] Preferably, the graphite particle size includes: 20 wt% particles with a particle size of 8-12 μm, 30 wt% particles with a particle size of 20-25 μm, and 50 wt% particles with a particle size of 15-18 μm.
[0021] By adopting the above technical solution, 15-18μm serves as the main skeleton, determining the median particle size of the graphite powder, ensuring the material's basic tap density and processing flowability, while also considering lithium-ion transport distance, and balancing rate performance and cycle stability. 8-12μm particles fill the gaps between large and medium-sized particles, achieving a denser particle packing effect, increasing electrode compaction density, and improving cell energy density. The larger specific surface area of the fine particles provides more rapid lithium-ion reaction sites, improving high-current discharge capability and matching the high-power output during drone takeoff.
[0022] A particle size of 20-25μm reduces the overall specific surface area of the powder, decreasing the contact area between the negative electrode and the electrolyte, inhibiting excessive SEI film growth, reducing initial irreversible capacity, and mitigating the risk of cell gas expansion. The increased proportion of coarse particles improves powder flowability and reduces abnormally high viscosity during slurry preparation. With 50 wt% medium-sized particles, 30 wt% large particles, and 20 wt% fine particles, the high packing density and excellent compaction density are beneficial for high energy density and long battery life in drones.
[0023] Preferably, the graphite after oxidation is pretreated as follows: the metal-organic framework material is placed in dilute nitric acid, stirred at room temperature, washed with water, and dried to obtain an activated metal-organic framework material; the activated metal-organic framework material is placed in an ethanol solution of nickel nitrate, stirred magnetically at room temperature, filtered, and dried; the dried powder is calcined to obtain a nano-nickel-supported porous carbon composite material. Graphite, nano-nickel-supported porous carbon composite material, tin dioxide, carbon nanotubes, and anhydrous ethanol were mixed, ground, dried, and sieved to obtain pretreated graphite.
[0024] By adopting the above technical solution, dilute nitric acid provides a weakly acidic environment, which lightly etches the surface of the metal-organic framework material crystal, creates defects and open pores on the particle surface, unblocks the blocked micropore channels, and increases the contact area of the channels.
[0025] Ethanol has a lower surface tension than water, allowing for more thorough wetting of the nanopores in the metal-organic framework (MOF) material, thus enabling Ni²⁺ to diffuse into the pores. Ni²⁺ is uniformly distributed within the micropores of the MOF framework, achieving molecular-level dispersion. The organic ligands in the MOF material undergo carbonization, transforming into a highly conductive nitrogen-doped porous carbon framework. At high temperature, nickel oxide (NiO) generated from the decomposition of nickel nitrate within the pores is reduced to metallic nano-nickel (Ni). 0The nickel ions are encapsulated within a carbon layer. Nickel ions are fully reduced to elemental nickel nanoparticles, which are embedded and anchored within the porous carbon channels. The porous carbon framework acts as a physical confinement mechanism, inhibiting the growth of Ni grains at high temperatures. The resulting product is a nano-nickel embedded porous carbon composite material.
[0026] Graphite serves as the structural framework, SnO2 provides ultra-high capacity, and nano-nickel-loaded porous carbon composite materials provide additional porous lithium storage sites and buffer volume changes. Carbon nanotubes construct a long-range conductive network. The mechanical shear force of ball milling uniformly mixes the components, allowing SnO2 and nano-nickel-embedded porous carbon composite materials to tightly coat the graphite surface, forming a core-shell composite structure. The ternary graded graphite matrix maintains high compaction density and high energy density, comprehensively meeting the three core requirements of drone batteries: high energy density, high-rate instantaneous discharge, and long-cycle safety and stability.
[0027] Preferred calcination conditions: heating to 445-450℃ at 2-3℃ / min and holding for 2-2.5h.
[0028] By adopting the above technical solution, the temperature rises gradually, and the organic ligands of the metal-organic framework material are gradually thermally decomposed and carbonized. This avoids the instantaneous collapse of the metal-organic framework material and the large-scale blockage of the pore structure caused by rapid temperature rise. At the same time, it prevents the rapid decomposition of nickel salts and the agglomeration of large-sized nickel particles, ensuring the generation of nanoscale nickel grains.
[0029] Preferably, by mass ratio, the ratio of graphite:nano-nickel supported porous carbon composite material:tin dioxide:carbon nanotubes is 100:5-6:12-13:2.
[0030] By adopting the above technical solutions, the main phase of natural flake graphite for lithium-ion storage ensures high overall high compaction density and low expansion of the negative electrode, providing the basic energy density for drone battery cells. The ternary particle size distribution ensures the powder packing density. The high conductivity of the internal nano-nickel constructs a high-speed conductive network, reduces the overall impedance of the electrode, and significantly improves the high-rate discharge capability, matching the high-power output of the drone during takeoff. The porous carbon derived from the metal-organic framework material provides abundant rapid lithium-ion transport channels. At the same time, as a flexible buffer matrix, it alleviates the huge volume expansion during SnO2 lithium insertion and extraction, and inhibits SnO2 pulverization and shedding.
[0031] SnO2 doping enhances the overall reversible capacity of composite materials, improving battery energy density and extending drone endurance; one-dimensional conductive fillers build continuous long-distance conductive pathways between graphite particles, compensating for contact resistance between particles; further improving rate performance; at the same time, carbon nanotubes also act as fiber toughening agents, buffering SnO2 volume stress and improving cycle stability.
[0032] The Ni nanoparticle and carbon nanotube dual conductive system has low impedance and excellent high current discharge. The metal-organic framework material-derived porous carbon buffer framework inhibits SnO2 volume expansion and pulverization, and improves long cycle life. The small amount of SnO2 doping improves the specific capacity of the negative electrode.
[0033] In summary, this application has the following beneficial effects: 1. This application features a three-stage particle size distribution and high-density lithium-ion exchange, which improves the energy density of individual battery cells and extends the flight time of drones. Oxidation with nitric acid and potassium permanganate activates the edges, resulting in faster lithium-ion conduction and meeting the requirements of high-current discharge and instantaneous power output for drones.
[0034] 2. In this application, nitric acid molecules are embedded in the graphite interlayer to form graphite interlayer compounds, which physically expand the interlayer spacing, reserving a wider channel for the rapid insertion and extraction of lithium ions and improving the high-rate discharge performance of drone batteries.
[0035] 3. In this application, potassium permanganate is used to lightly etch the graphite edges, opening a small number of interlayer channels, shortening the lithium-ion diffusion path, and improving fast charging capability. Detailed Implementation
[0036] The present application will be further described in detail below with reference to the embodiments.
[0037] The raw materials used in the examples and comparative examples are all commercially available.
[0038] Example 1 A process for preparing a graphite anode material for drone batteries includes the following steps: oxidizing graphite with nitric acid and potassium permanganate, wherein the graphite particle size includes: 20 wt% particles with a particle size of 8-12 μm, 30 wt% particles with a particle size of 20-25 μm, and 50 wt% particles with a particle size of 15-18 μm.
[0039] Specifically, the graphite is oxidized as follows: 1 kg of natural flake graphite is added to 10 L of 65 wt% concentrated nitric acid and stirred in an ice-water bath at 3°C for 10 min. 0.1 kg of potassium permanganate is added slowly in batches while maintaining the temperature at 3°C. After the addition is complete, stirring is continued for 35 min. The mixture is then cooled to room temperature, and 2 L of 1 M dilute hydrochloric acid is added to the precipitate. The mixture is stirred thoroughly for 5 min, separated by high-speed centrifugation (10000 rpm, 10 min), washed with deionized water until pH=7, and dried at 60°C. The dried graphite is then placed in a tube furnace, and high-purity argon gas is introduced. The temperature is increased to 400°C at 5°C / min and held for 50 min. The mixture is then allowed to cool naturally to obtain activated graphite.
[0040] Example 2: A preparation process for a graphite anode material for drone batteries. The difference from Example 1 is that the graphite particle size includes: 18 wt% particles with a particle size of 8-12 μm, 32 wt% particles with a particle size of 20-25 μm, and 50 wt% particles with a particle size of 15-18 μm.
[0041] Example 3: A preparation process for a graphite anode material for drone batteries, which differs from Example 1 in that the graphite particle size includes: 21 wt% particles with a particle size of 8-12 μm, 28 wt% particles with a particle size of 20-25 μm, and 51 wt% particles with a particle size of 15-18 μm.
[0042] Example 4: A preparation process for a graphite anode material for drone batteries, differing from Example 1 in that the graphite is oxidized. Specifically, 1.2 kg of natural flake graphite is added to 11 mL of 65 wt% concentrated nitric acid and stirred in an ice-water bath at 5°C for 12 min. 0.2 kg of potassium permanganate is added slowly in batches while maintaining the temperature at 5°C. After the addition is complete, stirring continues for 40 min. The mixture is then cooled to room temperature, and 2 L of 1 M dilute hydrochloric acid is added to the precipitate. The mixture is stirred thoroughly for 5 min, separated by high-speed centrifugation (10000 rpm, 10 min), washed with deionized water until pH=6, and dried at 60°C. The dried graphite is placed in a tube furnace, and high-purity argon gas is introduced. The temperature is increased to 400°C at 5°C / min and held for 60 min. The mixture is then naturally cooled to obtain activated graphite.
[0043] Example 5: A preparation process for a graphite anode material for drone batteries, which differs from Example 1 in that sulfuric acid can be added for oxidation treatment. The specific operation steps are as follows: In an ice-water bath at 5°C, slowly mix 11L of 65wt% concentrated nitric acid with 6kg of 98wt% concentrated sulfuric acid, stir until homogeneous, add 1kg of natural flake graphite, stir for 20 minutes in an ice-water bath at 5°C, then add 0.04kg of potassium permanganate, stir for 30 minutes at 5°C, and slowly add 25L of deionized water at a rate of 1 drop per second in an ice-water bath, and add 30wt% hydrogen peroxide (H2O2) dropwise until the solution turns bright yellow or light green and no bubbles are produced; Centrifuge at 10,000 rpm for 10 minutes, discard the supernatant, add 2 L of 1M dilute hydrochloric acid to the precipitate, stir and wash thoroughly for 5 minutes, wash with deionized water until pH=7, dry at 60℃, place the dried graphite in a tube furnace, introduce high-purity argon gas, heat to 400℃ at 5℃ / min, hold for 40 minutes, and cool naturally to obtain activated graphite.
[0044] Example 6: A preparation process for a graphite anode material for drone batteries, which differs from Example 1 in that sulfuric acid can be added for oxidation treatment. The specific operation steps are as follows: In an ice-water bath at 3°C, slowly mix 10L of 65wt% concentrated nitric acid with 9kg of 98wt% concentrated sulfuric acid until homogeneous. Add 1kg of natural flake graphite and stir for 20 minutes in the ice-water bath at 3°C. Then add 0.05kg of potassium permanganate and stir for 30 minutes at 3°C. In the ice-water bath, slowly add 25L of deionized water at a rate of 1 drop per second, and add 30wt% hydrogen peroxide (H2O2) dropwise until the solution turns bright yellow or light green and no bubbles are produced. Centrifuge at 10,000 rpm for 10 minutes, discard the supernatant, add 2 L of 1M dilute hydrochloric acid to the precipitate, stir and wash thoroughly for 5 minutes, wash with deionized water until pH=6, dry at 60℃, place the dried graphite in a tube furnace, introduce high-purity argon gas, heat to 400℃ at 5℃ / min, hold for 60 minutes, and cool naturally to obtain activated graphite.
[0045] Example 7: A preparation process for a graphite anode material for drone batteries. The difference from Example 5 is that the graphite after oxidation is pretreated as follows: 0.1 kg of metal-organic framework material ZIF-8 (purchased from Xi'an Qiyue Biotechnology Co., Ltd.) is placed in 10 L of 0.05 M dilute nitric acid, stirred at room temperature for 1 h, washed with water, and dried to obtain activated metal-organic framework material. The activated metal-organic framework material is placed in 0.3 L of 0.1 M nickel nitrate in ethanol solution, magnetically stirred and impregnated at room temperature for 24 h, filtered, and dried at 60 °C for 12 h. The dried powder is placed in a tube furnace, and an argon / hydrogen mixture (argon / hydrogen volume ratio 95:5) is introduced, heated to 450 °C at 2 °C / min, held for 2 h, and naturally cooled to obtain a nano-nickel-supported porous carbon composite material. Graphite, nano-nickel-supported porous carbon composite material, tin dioxide, 0.02 kg of carbon nanotubes, and anhydrous ethanol (liquid-solid ratio 3:1) were mixed and placed in a planetary ball mill and ground at 300 r / min for 4 hours. The grinding slurry was dried in a vacuum drying oven at 80℃ and passed through a 200-mesh sieve to obtain pretreated graphite.
[0046] By mass ratio, the ratio of graphite:nano-nickel supported porous carbon composite material:tin dioxide:carbon nanotubes is 100:5:12:2.
[0047] Example 8: A preparation process for a graphite anode material for drone batteries, differing from Example 5 in that the oxidized graphite is pretreated as follows: 0.1 kg of metal-organic framework material ZIF-8 is placed in 10 L of 0.05 M dilute nitric acid, stirred at room temperature for 2 h, washed with water, and dried to obtain activated metal-organic framework material. The activated metal-organic framework material is placed in 0.3 L of 0.1 M nickel nitrate in ethanol solution, magnetically stirred and impregnated at room temperature for 24 h, filtered, and dried at 60 °C for 12 h. The dried powder is placed in a tube furnace, an argon / hydrogen mixture is introduced, the temperature is raised to 450 °C, held for 2 h, and naturally cooled to obtain a nano-nickel-supported porous carbon composite material. Graphite, nano-nickel-supported porous carbon composite material, tin dioxide, 0.02 kg of carbon nanotubes, and anhydrous ethanol (liquid-solid ratio 3:1) were mixed and placed in a planetary ball mill and ground at 300 r / min for 4 hours. The grinding slurry was dried in a vacuum drying oven at 80℃ and passed through a 200-mesh sieve to obtain pretreated graphite.
[0048] Graphite:Nickel nanoparticle-supported porous carbon composite material:Tin dioxide:Carbon nanotubes = 100:6:13:2.
[0049] Example 9: A preparation process for a graphite anode material for drone batteries, which differs from Example 7 in that nickel nitrate is not added.
[0050] Example 10: A preparation process for a graphite anode material for drone batteries, which differs from Example 7 in that tin dioxide is not added.
[0051] Example 11: A preparation process for a graphite anode material for drone batteries, which differs from Example 7 in that carbon nanotubes are not added.
[0052] Comparative Example 1 A preparation process for a graphite anode material for drone batteries differs from Example 1 in that the graphite is oxidized using nitric acid.
[0053] Comparative Example 2 A preparation process for a graphite anode material for drone batteries differs from Example 1 in that 12 wt% of the particles have a diameter of 8-12 μm, 48 wt% of the particles have a diameter of 20-25 μm, and 40 wt% of the particles have a diameter of 15-18 μm.
[0054] The performance of a graphite anode material for drone batteries prepared in Examples 1-11 and Comparative Examples 1-2 was tested. 1. Tap density: The tap density of the graphite anode material was tested using a TF-100B tap tester.
[0055] 2. Using the high-rate graphite anode material of the examples and comparative examples as the anode and lithium sheet as the counter electrode, LIR2430 coin cells were fabricated. Charge and discharge tests were conducted in accordance with GB / T24533-2019 "Graphite Anode Materials for Lithium-ion Batteries". The initial discharge efficiency was measured under the conditions of 0.1C and 0.005-2.0V. The rate performance was evaluated by the discharge capacity ratio of 1C / 0.1C. The test results are shown in Table 1.
[0056] Table 1 Test data for the examples and comparative examples
[0057] As can be seen from Table 1, the graphite anode materials for UAV batteries prepared in Examples 1-4 of this application have good comprehensive performance. Among them, the tap density of Example 1 is 2.121 g / cm³. 3 The initial discharge efficiency is 92.7%, the rate performance is 91.3%, and the capacity retention rate after 500 cycles at 1C at room temperature is 89.5%. It is evident that the three-stage particle size distribution and high compaction density prepared in this application extend the drone's endurance. Oxidation with nitric acid and potassium permanganate activates the edges, resulting in faster lithium-ion conduction, meeting the requirements for high-current discharge and instantaneous power output in drones, and exhibiting excellent cycle performance.
[0058] Examples 5-6 were oxidized with sulfuric acid. As shown in Table 1, the tap density, first discharge efficiency, rate performance, and capacity retention of Examples 5-6 after 500 cycles at 1C at room temperature were all better than those of Examples 1-4. This indicates that the synergistic intercalation of sulfuric acid and nitric acid molecules more effectively expands the interlayer spacing of graphite, creating space for subsequent reactions and lithium-ion transport. The lithium-ion diffusion resistance is lower, and the high-rate discharge performance is better, making it suitable for the high-power output of UAVs during takeoff.
[0059] Examples 7-8 involved pretreatment of oxidized graphite, while Examples 9-11 involved the absence of nickel nitrate, tin dioxide, and carbon nanotubes, respectively. Table 1 shows that Examples 7-8 exhibited better tap density, initial discharge efficiency, rate performance, and capacity retention after 500 cycles at 1C at room temperature compared to Examples 5-6. However, Examples 9-11 showed better performance than Examples 5-6, but worse performance than Examples 7-8. This indicates that graphite serves as the structural framework, SnO2 provides ultra-high capacity, nano-nickel embedded in porous carbon composite materials provides additional porous lithium storage sites and buffers volume changes, carbon nanotubes construct a long-range conductive network, and the ternary graded graphite matrix maintains both high tap density and high energy density. Overall, this approach addresses the three core requirements of drone batteries: high energy density, high-rate instantaneous discharge, and long-cycle safety and stability.
[0060] Comparative Examples 1-2 involved oxidizing graphite with nitric acid and altering the particle size and range of the graphite particles. Table 1 shows that the tap density, initial discharge efficiency, rate performance, and capacity retention after 500 cycles at 1C at room temperature in Comparative Examples 1-2 were all inferior to those in Examples 1-4. This indicates that potassium permanganate slightly etched the graphite edges, opening a small number of interlayer channels, shortening the lithium-ion diffusion path, and improving fast-charging capability. The gradient particle size distribution is suitable for the high tap density, moderate specific surface area, fast-charging performance, and long cycle life required for drone power batteries.
[0061] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A preparation process for a graphite anode material for drone batteries, characterized in that, The process includes the following steps: oxidizing graphite with nitric acid and potassium permanganate, with the graphite particle size including: 18-22 wt% of particles with a particle size of 8-12 μm, 28-32 wt% of particles with a particle size of 20-25 μm, and 48-52 wt% of particles with a particle size of 15-18 μm.
2. The preparation process of a graphite anode material for a drone battery according to claim 1, characterized in that, The graphite is oxidized as follows: natural flake graphite is added to concentrated nitric acid, stirred in an ice-water bath, potassium permanganate is slowly added, stirring is continued, the temperature is lowered to room temperature, dilute hydrochloric acid is added to the precipitate, the mixture is stirred thoroughly, centrifuged, washed with deionized water, dried, and calcined to obtain activated graphite.
3. The preparation process of a graphite anode material for a drone battery according to claim 2, characterized in that, The ratio of natural flake graphite, potassium permanganate, and concentrated nitric acid is 1g:0.1-0.2g:10-11mL.
4. The preparation process of a graphite anode material for a drone battery according to claim 1, characterized in that, Sulfuric acid can also be added for oxidation treatment. The specific steps are as follows: In an ice-water bath, slowly mix concentrated nitric acid and concentrated sulfuric acid, stir evenly, add natural flake graphite, stir in an ice-water bath, then add potassium permanganate and stir, add deionized water and hydrogen peroxide in an ice-water bath until the solution turns bright yellow or light green and no bubbles are produced; centrifuge, discard the supernatant, add dilute hydrochloric acid to the precipitate, stir and wash thoroughly, dry, and calcine to obtain activated graphite.
5. The preparation process of a graphite anode material for a drone battery according to claim 1, characterized in that, The graphite particle size includes: 20 wt% particles with a particle size of 8-12 μm, 30 wt% particles with a particle size of 20-25 μm, and 50 wt% particles with a particle size of 15-18 μm.
6. The preparation process of a graphite anode material for a drone battery according to claim 1, characterized in that, The graphite after oxidation was pretreated as follows: the metal-organic framework material was placed in dilute nitric acid, stirred at room temperature, washed with water, and dried to obtain activated metal-organic framework material. The activated metal-organic framework material was placed in an ethanol solution of nickel nitrate, stirred magnetically at room temperature, filtered, and dried. The dried powder was calcined to obtain a nano-nickel-supported porous carbon composite material. Graphite, nano-nickel-supported porous carbon composite material, tin dioxide, carbon nanotubes, and anhydrous ethanol were mixed, ground, dried, and sieved to obtain pretreated graphite.
7. The preparation process of a graphite anode material for a drone battery according to claim 6, characterized in that, Calcination conditions: Increase the temperature to 445-450℃ at a rate of 2-3℃ / min and hold for 2-2.5 hours.
8. The preparation process of a graphite anode material for a drone battery according to claim 1, characterized in that, By mass ratio, the ratio of graphite:nanonickel-supported porous carbon composite material:tin dioxide:carbon nanotubes is 100:5-6:12-13:2.
